2021
DOI: 10.4314/wiojms.v20i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lactobacillus plantarum and Saccharomyces cerevisiae on growth improvement of hybrid Nile and Rufiji tilapia populations

Abstract: An investigation of the role of Lactobacillus plantarum and Saccharomyces cerevisiae on growth performance of hybrids from Oreochromis niloticus and Oreochromis urolepis urolepis was carried out in plastic tanks at 10 fish/m3 density and a salinity of 25 units. The probiotic treatments were 2, 4 and 6 g/kg feed while the control feed did not include any probiotics. Growth parameters were measured fortnightly and water quality parameters monitored every day. Survival rate and water quality factors revealed non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…This was in agreement with Essa et al 19 , where significantly higher growth performance was reported in O. niloticus fed to Lactobacillus plantarum, Mohapatra et al 20 , when fed to Labeo rohita. Similarly, growth and feed efficiency were reported to be higher in Oreochromis niloticus fed L. plantarum-based diets compared to the control group 21 .…”
Section: Discussionmentioning
confidence: 90%
“…This was in agreement with Essa et al 19 , where significantly higher growth performance was reported in O. niloticus fed to Lactobacillus plantarum, Mohapatra et al 20 , when fed to Labeo rohita. Similarly, growth and feed efficiency were reported to be higher in Oreochromis niloticus fed L. plantarum-based diets compared to the control group 21 .…”
Section: Discussionmentioning
confidence: 90%